Systematic evaluation of a panel of 30 synthetic cannabinoid receptor agonists structurally related to MMB‐4en‐PICA, MDMB‐4en‐PINACA, ADB‐4en‐PINACA, and MMB‐4CN‐BUTINACA using a combination of binding and different CB1 receptor activation assays—Part II: Structure activity relationship assessment via a β‐arrestin recruitment assay. Issue 7 (14th April 2021) - Grafinger, Katharina Elisabeth; Cannaert, Annelies; Ametovski, Adam; Sparkes, Eric; Cairns, Elizabeth; Banister, Samuel D.; Auwärter, Volker; Stove, Christophe P.
Abstract: Synthetic cannabinoid receptor agonists (SCRAs) are the second largest class of new psychoactive substances (NPS) and are associated with serious adverse effects and even death. Despite this, little pharmacological data are available for many of the most recent SCRAs. This study consists of three different parts, aiming to systematically evaluate a panel of 30 SCRAs using binding and different in vitro human cannabinoid 1 receptor (CB1 ) activation assays. The present Part II investigated the SCRA analogs for their CB1 activation via a β‐arrestin recruitment assay. The panel was systematically designed to include key structural sub‐features of recent SCRAs. Thus, the 4‐pentenyl tail of MMB‐4en‐PICA and MDMB‐4en‐PINACA was retained while incorporating varying head groups from other prevalent SCRAs, including amides and esters of L‐valine, L‐ tert ‐leucine, and L‐phenylalanine, and adamantyl and cumyl moieties. All 30 SCRAs activated CB1, with indazoles generally showing the greatest potency (EC50  = 1.88–281 nM), followed by indoles (EC50  = 11.5–2293 nM), and the corresponding 7‐azaindoles (EC50  = 62.4–9251 nM). Several subunit‐linked structure–activity relationships were identified: (i) tert ‐leucine‐functionalized SCRAs were more potent than the corresponding valine derivatives; (ii) no major difference in potency or efficacy was observed between tert ‐leucine/valine‐derived amides and the corresponding methyl esters; however, phenylalanine analogs were affected by this change; and (iii) minor structural changes to the 4‐pentenyl substituent had little influence on activity. These findings elucidate structural features that modulate the CB1 activation potential of currently prevalent SCRAs and a systematic panel of analogs, some of which may appear in NPS markets in future. Abstract : Investigation of a panel of 30 SCRA analogues for their human cannabinoid 1 receptor (CB1) activation potential via a β‐arrestin recruitment assay. The panel was systematically designed to include key structural sub‐features of recent SCRAs, with the chemical synthesis and characterization being presented in Part I of this study